2018
DOI: 10.15316/sjafs.2018.80
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different plant densities and nitrogen levels on certain macro and micro element contents of okra

Abstract: Field trials were conducted in two locations: the training fields of the Ege University Odemis Vocational High School and Ege University, Menemen Research, Application and Production Farm, where the effects of different plant densities and nitrogen levels on macro and micro element contents of okra (Abelmoschus esculentus L.) were investigated. The experiments were conducted using a split-plot design with three replicates, where the main plots consisted of nitrogen applications and sub-plots of plant densities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Many researchers study the growth, yield, and quality of Okra by comparing the impact of different plant densities, nitrogen level, soil, irrigation water salinity, irrigation intervals, salicylic acid, gibberellic acid, and organic manures, etc. Few references are [19,20,21,22,23]. Most of the existing research about yield and/or growth okra makes use of some basic statistics, graphical representations, One-way, Two-way, or repeated ANOVA with some multiple comparison tests.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers study the growth, yield, and quality of Okra by comparing the impact of different plant densities, nitrogen level, soil, irrigation water salinity, irrigation intervals, salicylic acid, gibberellic acid, and organic manures, etc. Few references are [19,20,21,22,23]. Most of the existing research about yield and/or growth okra makes use of some basic statistics, graphical representations, One-way, Two-way, or repeated ANOVA with some multiple comparison tests.…”
Section: Methodsmentioning
confidence: 99%
“…In the study, during plant growth, irrigation, hoeing and weed control were made according to Vural et al (2000); Yoldas et al (2018). In periods in which the trial was conducted, any disease or harmful effects were observed in okra plants.…”
Section: Maintenance Proceduresmentioning
confidence: 99%